Digital Media A Problem-solving Approach for Computer Graphics - Elias, Rimon (Springer International Publishing : Imprint: Springer, 2014)
Focusing on the computer graphics required to create digital media this book discusses the concepts and provides hundreds of solved examples and unsolved problems for practice. Pseudo codes are included where appropriate, but these coding examples do not rely on specific languages. The aim is to get readers to understand the ideas and how concepts and algorithms work, through practicing numeric examples. Topics covered include: 2D Graphics 3D Solid Modelling Mapping Techniques Transformations in 2D and 3D Space Illuminations, Lighting and Shading Ideal as an upper level undergraduate text, Digital Media - A Problem-solving Approach for Computer Graphics, approaches the field at a conceptual level thus no programming experience is required, just a basic knowledge of mathematics and linear algebra.